Crises não epiléticas psicogénicas em doentes avaliados numa Unidade de Monitorização de Epilepsia - Diogo Vaz da Silva Cardoso da Silva (2022)
Psychogenic Nonepileptic Seizures (PNES) in patients evaluated in an Epilepsy Monitoring Unit Diogo Silva1, Leonor Dias1,2, Marta Carvalho1,2, Ricardo Rego2,3, Helena Rocha2,3 1-Department of Clinical Neurosciences and Mental Health, Faculty of Medicine of University of Porto 2-Department of Neurology, Centro Hospitalar Universitário de São João, EPE 3-Neurophysiology Unit, Department of Neurology, Centro Hospitalar Universitário de São João, EPE Introduction: Psychogenic nonepileptic seizures (PNES) are paroxysmal events often confused with seizures. Misdiagnosis can lead to inappropriate treatment with antiseizure drugs (ASD). Video-electroencephalogram monitoring (VEM) in an Epilepsy Monitoring Unit (EMU) allows optimizing the diagnosis and consequently the treatment. Aim: to characterize a cohort of patients with PNES evaluated in the EMU and to assess the clinical outcome after VEM. Methods: Retrospective descriptive analysis of patients with PNES evaluated in the EMU between 2011-2020. Results: Of the 456 VEM performed, we included 28, totaling 64 PNES (mean 2/patient). The mean duration of VEM was 48h (SD 28.4). Most were female (86%) with a mean age of 41 years (SD 14.3). The mean age of PNES onset was 32 years (6-60 years), with a mean time to diagnosis of 12 years (SD 10.3). Most patients had motor and non-motor events (60.9%). The movements were mostly focal (85.7%), non-rhythmic (53.6%) and with alternating patterns (42.9%). Pelvic thrusting was rare (7%). Fifteen patients (54%) did not identify precipitants. At the time of VEM, 12 (42.9%) patients were diagnosed as having epilepsy only. Ninety-six percent of patients were on ASD, which were multiple in 64%. After VEM, 18 (64.2%) patients changed their diagnosis and 46% discontinued ASD. During follow-up (mean 3.5 years; SD 2.4), 36% of patients reported symptomatic improvement and 11% resolution of PNES. Conclusion: Analysis of paroxysmal events during VEM combined with patient history allowed a more accurate diagnosis of PNES, leading to discontinuation of ASD in almost half of patients.